Triple-Entry Accounting Based on Blockchain Technology: How Can It Be Implemented in Indonesia? - Ananta Wahyu Sasongko; Putriana Sriwijianingsih; Farhani Kautsar Nugraha (Global Financial Accounting Journal, 2023)
Purpose - This study focuses on finding solutions for Indonesian accountants to apply triple-entry accounting (TEA) based on blockchain technology (BT). The aim of this study is to raise the general level of understanding and awareness about Blockchain Technology (BT)-based Triple-Entry Accounting (TEA). Furthermore, this article explores the possibility of implementing BT-based TEA in Indonesia, which still uses the double-entry accounting (DEA) system in daily practice. Research Method - This study used a qualitative methodology as a literature review and case study to analyze various academics' theories, attitudes, and opinions on TEA. Findings - The TEA method has undergone extensive research worldwide and offers benefits far superior to the double-entry accounting system (DEA), which the accounting industry has employed for over five centuries. However, the lack of a legal framework in Indonesia and the possible high cost of recognition means that the implementation of a BT-based TEA in Indonesia has yet to start. Implication - This research was conducted to help accountants, regulators, and business researchers know the role of BT in the potential implementation of TEA and the need to implement it to develop a new accounting system that provides better usability, security, and predictive functions than DEA. We also want to motivate more accounting researchers, accounting practitioners, and accounting regulators in Indonesia to get to know and further apply BT in accounting. We hope this article can generate insights into the knowledge and insights on implementing the BT-based TEA system.